The relevance of the data collection process in the VioGén system from a feminist perspective - Pereira, Javiera Farías (Oñati Socio-Legal Series, 2024)
The VioGén system is a predictive policing and algorithm tool, which has been implemented in Spain since 2007. Its main objective is to assess the risk of a woman of being victim of intimate partner violence and proposing measures for her protection accordingly. This work will focus on one of the most essential parts of the tool’s functioning: the data collection process. I intend to illustrate how this process of data collection can be influenced by the bias and stereotypes that have been constructed within criminal law concerning gender violence victims and the way this affects, in the end, the system’s functioning.